Current considerations on diagnosis, and treatment of thyroid cancer - Ramiro Julio Bejerano; Héctor Manuel Camué Ciria (Revista Cubana de Medicina Militar)
Introduction: Since the beginning of this century there has been a notable increase worldwide in the incidence rate of thyroid cancer, which generally has a latent and asymptomatic course. Objectives: To deepen the knowledge of the novel aspects of timely diagnosis and treatment of thyroid cancer. Development: Thyroid cancer is the most frequent malignant disease of the endocrine system. In recent decades, its incidence has increased rapidly, although mortality has remained low. The discovery and development of new imaging, immunological and molecular techniques have made it possible to study thyroid neoplasm in depth. This has favored advancing in the aspects that have most modified the new attitude regarding timely diagnosis and its treatment. Conclusions: In recent years, advances in basic, clinical and translational research have transformed old concepts related to thyroid cancer and have equipped with new tools for timely diagnosis and personalized treatment.